Conjuntura fiscal do Município de Fortaleza: uma análise da sustentabilidade da dívida pública no período de 2008 a 2019 - Mendes, Raphael Aleixo (2020)
The Brazilian economy has been going through several changes in the recent years, especially about public finances. The federal constitution gave more autonomy to federal, state and municipal governments for to propose budget, in the collection and regularization of taxes as well as to get or to accept debts and other expenses submitted to principles, seals, norms, and limits that will be created through Complementary Laws. The Fortaleza municipality has capturing news credit operations in recent years, where it's necessary to analyze the inflow and outflow of their income and expenses whether the municipality's indebtedness occurs in a sustainable way compared to the fiscal results of the last financial years as well as the municipality fiscal solvency. This study aims to analyze the principal revenues and expenses comportment, debt and investments and how the fiscal policy realized by municipality gives the equilibrium to their public finances through the Fiscal Reaction Function. Using the fiscal reaction model it was analyzed if there is statistically the solvency the Fortaleza’s municipal public debt. It was analyzed variables such as Total Revenue and Net Current Revenue on the revenue side. On the expenses side, expenses with personnel expenses and social charges, interest, and debt charges, the consolidated debt and the amount of investment realized by the municipality, where these items are fundamental to the sustainability and fiscal balance of the municipality's fiscal management.